Formation of student’s self-education and competence in the process of developing mental skills - Aliyeva Ruhangiz Mammad (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2023)
Self-education is aimed at heights and perfection, self-education puts simpler issues. An impulsive person with an explosive character gets used to not yelling, self-control helps – this is self-education. A calm and adequate person teaches himself/herself wisdom – this is self-education. The child teaches himself/herself not to lie and not to fight – this is self-education. A young graduate of the conservatory willingly performs transitions masterfully day after day – this is self-improvement. Self-education is the first step towards self-development. Self-education is one of the very necessary links of a single complex of intellectual labour. This type of activity, which includes the elements of independent activity, has been the centre of attention in all structures and stages of social life as a means of improving a person's socio-political and professional-specialization training and acquiring knowledge, it has always engaged people with progressive views and has been highly valued based on its usefulness “coefficient”. It is necessary to perform the opposite operation in the mental work process. In addition to giving these operations a great place in training, the teacher should also take care of their formation in students. Insufficient development of students’ analysis-composition activities negatively affects not only the depth of their knowledge, but also the level of their skills. The purpose of the article is to examine the high demands placed on school preparation in the era of scientific and technical progress, in a situation where information is growing rapidly. In addition to arming the young generation with scientific knowledge, the school should teach them to acquire independent knowledge, free work habits, intellectual work culture, independence of thought, self-education habits, and better prepare for independent work activities. This is one of the important directions of educational reforms.